Study of a numerical integration method using the compact scheme for electromagnetic transient simulations - Tanaka, Yohei; Baba, Yoshihiro (Electric power systems research, 2023)
•Transient simulations are important for power system analysis.•The numerical integration method is required to obtain the time solution.•The use of differential values improves the accuracy and numerical stability. This paper proposes a one-stage and oscillation free numerical integration method using the compact scheme for electromagnetic transient simulations. Since the compact scheme becomes L-stable at a moment when a circuit suddenly changes to a stiff system, the method is capable of suppressing the spurious numerical oscillations. Moreover, the compact scheme, which is a one-stage method, does not produce spurious spikes due to nonlinear elements. The compact scheme is compared with the trapezoidal method, the two-stage diagonally implicit Runge-Kutta (2S-DIRK) and the trapezoidal method with the second order backward difference formula (TR-BDF2). It follows from the comparison that the compact scheme does not produce the spurious numerical oscillations and spikes.